Coleridge's notebooks : a selection - Coleridge, Samuel Taylor, 1772-1834 (Oxford University Press, 2002)
"Samuel Taylor Coleridge was one of the Romantic age's most enigmatic figures, a genius of astonishing diversity; author of some of the most famous poems in the language; co-author, with Wordsworth, of Lyrical Ballads; one of Britain's greatest critics and theorists of literature and the imagination; as well as autobiographer, nature-writer, philosopher, theologian, psychologist, and talker. Throughout his life, he confided thoughts and emotions to his Notebooks, where we can still see his speculations and observations taking shape. This edition presents a selection from this unique work, newly presented, with notes and commentary, for the student as well as the general reader."--Jacket